In-situ F-doped FeOCl layered material as well as preparation method and application thereof

By doping F atoms in situ in FeOCl to form an F-doped FeOCl photocatalyst, the problems of low utilization rate and poor stability of the existing catalyst H2O2 are solved, and efficient photofenton activity and structural stability are achieved.

CN119455991AActive Publication Date: 2025-02-18NANJING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411584746.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing heterogeneous Fenton catalysts have problems such as low H2O2 utilization, low Fenton activity and poor stability, and the structural stability of the catalyst decreases after intercalation modification.

Method used

By doping F atoms in situ in FeOCl, an F-doped FeOCl photocatalyst is formed, and the electron density of the ferrite layer is improved by using the strong electronegativity of F atoms to improve the catalytic performance.

Benefits of technology

It achieves efficient photofenton activity and good structural stability, can effectively catalyze H2O2 to degrade organic pollutants, and has good cyclicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455991A_ABST
    Figure CN119455991A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ F-doped FeOCl layered material as well as a preparation method and application thereof, FeCl3 and fluoride salt are calcined in oxygen-containing gas, and the in-situ F-doped FeOCl layered material can be obtained. The F-doped FeOCl layered material prepared by the invention has the advantages of high photo-Fenton activity, good cyclicity and the like, and can efficiently activate H2O2 to degrade organic pollutants in water under an illumination condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of environmental functional materials, and specifically relates to an in-situ F-doped FeOCl layered material, and a preparation method and application thereof. Background Art

[0002] As a type of advanced oxidation technology (AOP), Fenton oxidation technology degrades organic pollutants by producing hydroxyl radicals with strong oxidizing properties. It has the advantages of high efficiency and simple operation. The traditional homogeneous Fenton system has problems such as narrow pH response range, difficulty in separating and recovering the catalyst, and a large amount of iron sludge generated during the reaction process causing secondary pollution. The heterogeneous Fenton technology can effectively overcome the above defects. At present, heterogeneous Fenton catalysts are mainly iron-based catalysts, including metal oxides (Fe2O3, Fe3O4, FeOOH), zero-valent iron, iron sulfide, etc. However, these heterogeneous Fenton catalysts still have shortcomings such as low H2O2 utilization, low Fenton activity and poor stability.

[0003] FeOCl is a typical layered material. In its structure, each Fe atom is coordinated with 4 O atoms and 2 Cl atoms to form a cis-[FeO4Cl2] octahedron. The octahedra share OO or O-Cl edges to form a double layer. A layer of Cl atoms is densely stacked outside the double layer. The layers are connected by electrostatic force or van der Waals force. Since van der Waals force is an intermolecular force with a weak action strength, it has a rich modulation space. The main Fe element in FeOCl has a high environmental abundance, flexible valence state changes, and is non-toxic and harmless. However, its layered stacking structure will result in its effective active area not being fully exposed, and there are problems such as slow Fe(III) / Fe(II) cycle and poor stability.

[0004] At present, most studies focus on intercalation modification of FeOCl to improve its Fenton activity. Chinese patent document CN117000303A discloses FeOCl catalytic materials and preparation methods of organic molecule intercalation, inserting organic molecules into the layered structure of FeOCl, and significantly expanding the interlayer spacing of the resulting catalyst, showing good performance in activating H2O2 to degrade pollutants, but the FeOCl of alcohol molecule intercalation has a lower crystallinity than that of unintercalated FeOCl. Yang Xuejing et al. (Journal of the American Chemical Society. 2022, 144, 4294-4299) introduced potassium ions into the FeOCl layered structure through KI redox intercalation, realizing the precise modulation of the iron coordination environment, thereby improving its catalytic performance, but the FeOCl photo-Fenton system of K ion intercalation has a Fe leakage of 1.4ppm. Zhang Wei et al. (Applied Catalysis B: Environmental. 2024, 345, 123701) also embedded hydroxylamine (HA) in the FeOCl layered structure, and then constructed a distorted two-dimensional surface to improve the activation performance of the catalyst by regulating the electronic structure of the iron site. However, the Fe leakage of the HA-intercalated FeOCl Fenton system after the reaction reached 1.12 ppm. Therefore, although the catalytic performance of the original FeOCl can be effectively improved by the intercalation modification method, the material lattice expands and the unit cell changes after intercalation, resulting in a decrease in the stability of the catalyst structure. Summary of the invention

[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide an in-situ F-doped FeOCl photocatalyst with high photo-Fenton activity and good stability. Another purpose of the present invention is to provide a simple method for preparing the F-doped FeOCl photocatalyst. Another purpose of the present invention is to provide an application of the F-doped FeOCl photocatalyst in degrading organic pollutants in wastewater.

[0006] The specific technical solutions of the present invention are as follows: A method for preparing an in-situ F-doped FeOCl layered material comprises calcining FeCl3 and a fluoride salt in an oxygen-containing gas, and further comprising the steps of washing the calcined product with water and drying it.

[0007] The oxygen-containing gas may be oxygen or air.

[0008] In the preparation method of the present invention, the fluoride salt is preferably selected from one or more of FeF3, NH4F and NaF, more preferably FeF3.

[0009] In the preparation method of the present invention, the molar ratio of FeCl3 to fluoride salt is preferably (9.1-9.9):(0.9-0.1), and more preferably (9.3-9.7):(0.7-0.3).

[0010] In a specific example of the present invention, the fluoride salt is selected from FeF3, and the molar ratio of FeCl3 to FeF3 is 9.7:0.3.

[0011] The preparation method of the present invention preferably has a calcination temperature of 150 to 300° C., a heating rate of 10° C. / min, and a calcination time of 0.5 to 4 h.

[0012] In a specific example of the present invention, the calcination temperature is 220° C., the heating rate is 10° C. / min, and the calcination time is 2 h.

[0013] The present invention also provides an in-situ F-doped FeOCl layered material, which is prepared by the method of the present invention.

[0014] The present invention also provides the use of the in-situ F-doped FeOCl layered material as a catalyst in removing organic pollutants in water.

[0015] In a specific application, the in-situ F-doped FeOCl layered material is used as a photo-Fenton catalyst to remove pollutants in water. The organic pollutants are selected from antibiotics, organic dyes, and phenols.

[0016] In the field of water treatment, photo-Fenton technology can be used to treat various organic pollutants and some inorganic pollutants, such as benzene, phenol, dyes, pesticides, etc. In particular, in the photo-Fenton process, H2O2 produces hydroxyl radicals, which effectively remove pollutants such as pesticides, dyes, drugs, nitrobenzene and chlorophenol. In addition, Fenton reagents are also widely used in the treatment of industrial wastewater, including oily wastewater, printing and dyeing wastewater, coking wastewater, phenolic wastewater, and nitro wastewater.

[0017] The organic pollutants are selected from antibiotics, organic dyes, phenols, etc. For example, tetracycline, macrolide antibiotics, quinolone antibiotics (such as ciprofloxacin, ofloxacin), methylene blue, rhodamine B, methyl orange, phenol. In a specific example of the present invention, the organic pollutants are selected from tetracycline, ciprofloxacin, norfloxacin, sulfamethoxazole, 2,4-dichlorophenol, 2,4,6-trichlorophenol, phenol, bisphenol A, and p-fluorophenol.

[0018] The treatment steps are as follows: the in-situ F-doped FeOCl layered material is uniformly dispersed in an aqueous solution containing organic pollutants and H2O2 is added, and catalytic degradation is carried out under light conditions.

[0019] Beneficial effects of the present invention: 1. The present invention provides an in-situ strongly electronegative atom-doped FeOCl photocatalyst. Compared with the intercalation-modified FeOCl photocatalyst in the prior art, the strongly electronegative atoms can directly partially replace the Cl in FeOCl without causing distortion of its layered structure. While regulating the electron density of the Fe site, the stability of its original structure can be maintained.

[0020] 2. In the present invention, F atoms are used to replace some Cl atoms in the original FeOCl. Since F atoms have the strongest electronegativity, the electron density of the iron oxide layer can be improved, thereby enhancing the Fenton-like activity.

[0021] 3. The F-doped FeOCl photocatalyst of the present invention is used to treat organic pollutants. Under light conditions, it can effectively catalyze and activate H2O2 to degrade pollutants in the solution, and has the advantages of high photo-Fenton activity and good recyclability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 1 is the XRD diagram of F-doped FeOCl (3% F-FeOCl) in Example 1 of the present invention and FeOCl in Comparative Example 1.

[0024] Figure 2 This is a scanning electron microscope image of F-doped FeOCl (3% F-FeOCl) in Example 1 of the present invention.

[0025] Figure 3 TEM, HRTEM and EDS element distribution images of F-doped FeOCl (3% F-FeOCl) in Example 1 of the present invention, wherein (a) is a TEM image, (b) is a HRTEM image, and (c) is an EDS element distribution image.

[0026] Figure 4 1 and 2 are XPS graphs of F-doped FeOCl (3% F-FeOCl) in Example 1 of the present invention, wherein (a) is the Fe2p fine spectrum, (b) is the O1s fine spectrum, (c) is the F1s fine spectrum, and (d) is the Cl 2p fine spectrum.

[0027] Figure 5 This is a performance diagram of photo-Fenton degradation of 4-chlorophenol by F-doped FeOCl (1-9% F-FeOCl) in Application Example 1 of the present invention.

[0028] Figure 6 This is a performance diagram of photo-Fenton degradation of 4-chlorophenol by F-doped FeOCl (3% F-FeOCl, ab-3% F-FeOCl) in Application Example 2 of the present invention.

[0029] Figure 7This is a performance diagram of photo-Fenton degradation of 4-chlorophenol by F-doped FeOCl (3% F-FeOCl, ce-3% F-FeOCl) in Application Example 3 of the present invention.

[0030] Figure 8 This is a performance diagram of photo-Fenton degradation of 4-chlorophenol by F-doped FeOCl (3% F-FeOCl, fh-3% F-FeOCl) in Application Example 4 of the present invention.

[0031] Fig. 9 The graphs are the cycle performance of photo-Fenton degradation of 4-chlorophenol by F-doped FeOCl (3% F-FeOCl) in Application Example 5 of the present invention and the comparison graphs of Fe leakage after Fenton reaction of different FeOCl-modified materials, wherein (a) is the cycle performance graph and (b) is the comparison graph of Fe leakage.

[0032] Fig.10 This is a performance diagram of photo-Fenton degradation of different organic pollutants by F-doped FeOCl (3% F-FeOCl) in Application Example 6 of the present invention. DETAILED DESCRIPTION

[0033] The technical scheme in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. The various terms and phrases used in the present invention have the general meanings known to those skilled in the art. The present invention provides a general or specific description of the materials and test methods used in the test. Although many materials and operating methods used to achieve the purpose of the present invention are well known in the art, the present invention is still described as detailed as possible herein. The instruments, reagents, materials, etc. involved in the following embodiments, unless otherwise specified, are conventional instruments, reagents, materials, etc. existing in the prior art, and unless otherwise specified, are conventional experimental methods, detection methods, etc. existing in the prior art. XPA-7 photochemical reactor was purchased from Nanjing Xujiang Electromechanical Factory.

[0034] Example 1 (1) 9.7 mmol FeCl3 and 0.3 mmol FeF3 were mixed uniformly; (2) The mixture was placed in air, heated at a rate of 10°C / min, and maintained at 220°C for 2h. The obtained product was washed with water and then dried to obtain a F-doped FeOCl photocatalyst, which was labeled as 3% F-FeOCl.

[0035] Example 2 Example 2 is basically the same as Example 1, except that the molar ratio of FeCl3 to FeF3 is 9.9:0.1, and the remaining steps and raw materials are the same as Example 1. The obtained material is marked as 1% F-FeOCl.

[0036] Example 3 Example 3 is basically the same as Example 1, except that the molar ratio of FeCl3 to FeF3 is 9.5:0.5, and the remaining steps and raw materials are the same as Example 1. The obtained material is marked as 5% F-FeOCl.

[0037] Example 4 Example 4 is basically the same as Example 1, except that the molar ratio of FeCl3 to FeF3 is 9.3:0.7, and the remaining steps and raw materials are the same as Example 1. The obtained material is marked as 7% F-FeOCl.

[0038] Example 5 Example 5 is basically the same as Example 1, except that the molar ratio of FeCl3 to FeF3 is 9.1:0.9, and the remaining steps and raw materials are the same as Example 1. The obtained material is marked as 9% F-FeOCl.

[0039] Example 6 Example 6 is basically the same as Example 1, except that NH4F is used as the fluoride salt. The remaining steps and raw materials are the same as those of Example 1. The obtained material is marked as a-3%-FeOCl.

[0040] Example 7 Example 7 is basically the same as Example 1, except that NaF is used as the fluoride salt. The remaining steps and raw materials are the same as those of Example 1. The obtained material is marked as b-3% F-FeOCl.

[0041] Example 8 Example 8 is basically the same as Example 1, except that the calcination temperature is 150° C., and the remaining steps and raw materials are the same as those of Example 1. The obtained material is marked as c-3% F-FeOCl.

[0042] Example 9 Example 9 is basically the same as Example 1, except that the calcination temperature is 260° C., and the remaining steps and raw materials are the same as those of Example 1. The obtained material is marked as d-3% F-FeOCl.

[0043] Example 10 Example 10 is substantially the same as Example 1, except that the calcination temperature is 300° C., and the remaining steps and raw materials are the same as those of Example 1. The obtained material is labeled as e-3% F-FeOCl.

[0044] Embodiment 11 Example 11 is basically the same as Example 1, except that the calcination time is 0.5 h. The remaining steps and raw materials are the same as those of Example 1. The obtained material is marked as f-3% F-FeOCl.

[0045] Example 12 Example 12 is basically the same as Example 1, except that the calcination time is 4 h. The remaining steps and raw materials are the same as those of Example 1. The obtained material is marked as g-3% F-FeOCl.

[0046] Example 13 Example 13 is basically the same as Example 1, except that the calcination time is 8 h. The remaining steps and raw materials are the same as those of Example 1. The obtained material is marked as h-3% F-FeOCl.

[0047] Comparative Example 1 A FeOCl photocatalyst is prepared by the following steps: (1) Grind 10 mM FeCl3 evenly; (2) placing it in air, heating it at a rate of 10°C / min, and maintaining it at 220°C for 2h. The obtained product was washed with water and then vacuum dried to obtain a FeOCl photocatalyst, which was recorded as FeOCl.

[0048] The XRD patterns of F-doped FeOCl (3% F-FeOCl) in Example 1 of the present invention and FeOCl in Comparative Example 1 are shown in FIG. Figure 1 As shown. Figure 1 It can be seen that compared with FeOCl, the diffraction peak position and intensity of 3% F-FeOCl have not changed, indicating that the method of replacing Cl atoms with F atoms will not destroy the original crystal structure of FeOCl.

[0049] The scanning electron microscope image of F-doped FeOCl (3% F-FeOCl) in Example 1 of the present invention is as follows: Figure 2 As shown. Figure 2 It can be seen that 3% F-FeOCl has a rod-like structure.

[0050] The transmission electron microscopy, high-resolution transmission electron microscopy and EDS element distribution images of F-doped FeOCl (3% F-FeOCl) in Example 1 of the present invention are as follows: Figure 3 shown. Figure 3 a shows that 3% F-FeOCl has a rod-like structure. Figure 3 b The iron oxide layer structure can be clearly observed, which proves that FeOCl is successfully synthesized and F doping does not destroy its original layered structure. Figure 3 The uniform distribution of each element in c confirms the successful doping of F.

[0051] The XPS graph of F-doped FeOCl (3% F-FeOCl) in Example 1 of the present invention is as follows: Figure 4 shown. Figure 4a is the Fe2p fine spectrum, where it can be observed that iron exists in the form of both ferrous iron and ferric iron; Figure 4 b is the O1s fine spectrum, and the diffraction peak attributed to MO is observed at 529.77 eV; Figure 4 c is the F1s fine spectrum, indicating the successful doping of F element; Figure 4 d is the Cl 2p fine spectrum, and diffraction peaks attributed to M-Cl were observed at 198.32 eV and 199.91 eV.

[0052] Application Example 1 The photocatalysts obtained in Examples 1 to 5 were used to degrade 4-chlorophenol. The specific experimental conditions were: 10 mg of the catalyst was placed in 50 mL of 0.1 mM 4-chlorophenol solution, and the adsorption-desorption equilibrium was reached after 30 min. Then 50 μL of H2O2 solution (3 mM) was added, and the xenon lamp was turned on to perform the photo-Fenton reaction. The results are shown in FIG. Figure 5 The results show that with the increase of F doping concentration, the removal performance of 4-chlorophenol by the photo-Fenton system of different catalysts first increases and then decreases. 3% F-FeOCl shows the best catalytic performance, with a removal rate of 100% in 30 minutes.

[0053] Application Example 2 The photocatalysts obtained in Examples 1 and 6-7 were used to degrade 4-chlorophenol. The specific experimental conditions were: 10 mg of the catalyst was placed in 50 mL of 0.1 mM 4-chlorophenol solution, and the adsorption-desorption equilibrium was reached after 30 min. Then 50 μL of H2O2 solution (3 mM) was added, and the xenon lamp was turned on to perform the photo-Fenton reaction. The results are shown in FIG. Figure 6 The results show that the photo-Fenton activities of catalysts prepared with different F precursors are significantly different, among which 3% F-FeOCl prepared with FeF3 as a precursor exhibits the best catalytic performance.

[0054] Application Example 3 The photocatalysts obtained in Examples 1, 8 to 10 were used to degrade 4-chlorophenol. The specific experimental conditions were: 10 mg of the catalyst was placed in 50 mL of 0.1 mM 4-chlorophenol solution, and the adsorption-desorption equilibrium was reached after 30 min. Then 50 μL of H2O2 solution (3 mM) was added, and the xenon lamp was turned on to perform the photo-Fenton reaction. The results are shown in FIG. Figure 7 The results show that when the calcination temperature increases from 150°C to 300°C, the catalytic activity of the prepared 3% F-FeOCl first increases and then decreases, so the calcination temperature is preferably 220°C.

[0055] Application Example 4 The photocatalysts obtained in Examples 1 and 11 to 13 were used to degrade 4-chlorophenol. The specific experimental conditions were: 10 mg of the catalyst was placed in 50 mL of 0.1 mM 4-chlorophenol solution, and the adsorption-desorption equilibrium was reached after 30 min. Then 50 μL of H2O2 solution (3 mM) was added, and the xenon lamp was turned on to perform the photo-Fenton reaction. The results are shown in FIG. Figure 8 The results show that as the calcination time increases, the catalytic activity of the prepared 3% F-FeOCl first increases and then decreases, so the calcination time is preferably 2 h.

[0056] Application Example 5 This example aims to characterize the cyclic stability of the catalyst.

[0057] Taking the F-doped FeOCl photocatalyst (3% F-FeOCl) prepared in Example 1 as an example, its stability was investigated through a recycling experiment. The degradation experimental conditions were the same as those in Application Example 1. The catalyst of the photo-Fenton reaction was filtered and dried, and then the next cycle of degradation experiment was carried out under the same reaction conditions. This was repeated 5 times. The results are shown in FIG. Fig. 9 The results show that after 5 cycles, the removal rate of 4-chlorophenol in the 3% F-FeOCl photo-Fenton system can still reach 100% after 40 minutes, indicating that 3% F-FeOCl has good stability.

[0058] The Fe leakage after the Fenton reaction of FeOCl and F-doped FeOCl was further detected by referring to the method disclosed in the literature (Journal of the American Chemical Society. 2022, 144, 4294-4299), and compared with K-FeOCl (Journal of the American Chemical Society. 2022, 144, 4294-4299) and HA-FeOCl (Applied Catalysis B: Environmental. 2024, 345, 123701). The results are as follows: Fig. 9 The results show that the Fe leakage of F-doped FeOCl after Fenton reaction is only 0.38 ppm, which is much lower than that of K-FeOCl (Fe leakage is 1.4 ppm) and HA-FeOCl (Fe leakage is 1.12 ppm), indicating that the in-situ substitution strategy of strongly electronegative atoms can effectively solve the problem of decreased structural stability of FeOCl intercalation modified materials.

[0059] Application Example 6 This example aims to characterize the degradation effect of the catalyst on different phenolic pollutants.

[0060] Taking the F-doped FeOCl (3% F-FeOCl) prepared in Example 1 as an example, its degradation effect on different organic pollutants was investigated. The degradation experimental conditions were the same as those in Application Example 1, except that the pollutant used was any one of tetracycline (TC), ciprofloxacin (CIP), norfloxacin (NFX), sulfamethoxazole (SMZ), 2,4-dichlorophenol (2,4-DCP), 2,4,6-trichlorophenol (2,4,6-TCP), phenol (Phenol), bisphenol A (BPA), and p-fluorophenol (4-FP). The results are as follows. Fig.10 The results show that after 40 minutes of photo-Fenton reaction, the degradation rates of various organic pollutants (tetracycline, ciprofloxacin, norfloxacin, sulfamethoxazole, 2,4-dichlorophenol, 2,4,6-trichlorophenol, phenol, bisphenol A, and p-fluorophenol) by F-doped FeOCl (3% F-FeOCl) were all higher than 99%, showing good broad-spectrum performance.

Claims

1. A method for preparing an in-situ F-doped FeOCl layered material, characterized in that It is made by calcining FeCl3 and fluoride salt in oxygen-containing gas.

2. The preparation method according to claim 1, characterized in that The fluoride salt is selected from one or more of FeF3, NH4F and NaF.

3. The preparation method according to claim 1, characterized in that The molar ratio of the FeCl3 to the fluoride salt is (9.1-9.9):(0.9-0.1).

4. The preparation method according to claim 1, characterized in that The calcination temperature is 150-300°C, the heating rate is 10°C / min, and the calcination time is 0.5-4h.

5. An in-situ F-doped FeOCl layered material, characterized in that The method is prepared by any one of claims 1 to 4.

6. Use of the in-situ F-doped FeOCl layered material according to claim 5 as a catalyst in removing organic pollutants in water.

7. The use according to claim 6, characterized in that The treatment steps are as follows: the in-situ F-doped FeOCl layered material is uniformly dispersed in an aqueous solution containing organic pollutants and H2O2 is added, and catalytic degradation is carried out under light conditions.

8. The use according to claim 7, characterized in that The organic pollutants are selected from antibiotics, organic dyes, and phenols.

Citation Information

Patent Citations

  • Fluorine modified Fe3O4 magnetic nano material and preparation method and applications thereof

    CN108404942A

  • Preparation method of carbon-doped iron oxychloride composite material

    CN115770593A

  • Customized Health Care System

    KR1020230016761A

  • Battery containing a metal anode and an electrolyte providing high rates of metal electrolysis at near ambient temperatures

    US4882244A